A Review on Uses of Various Nanoparticlesin the Treatment of Rheumatoid Arthritis - Bairagi, Shriram; Takarkhede, Smita; Dighe, Jagruti; Gangurde, Dhaneshwari (Asian Journal of Pharmaceutical Research and Development, 2022)
Rheumatoid arthritis (RA) is a most common autoimmune (auto-self: immune-immunity system). It is inflammatory in nature. If generally causes bone and cartilage destruction. Itaffect on joint clinical manifestationsof arthritis various from patient to patient. Now, new field comes into existence called use of nanoparticles and nanotechnology. It improves the pharmacokinetic as well as pharmacodynamics of rheumatoid arthritis drugs. Nanoparticles act on site of inflammation and delivery of therapeutic agent to that site. It also increases specificity of drugs and decrease side effects. These review summarize the current therapeutic strategies for rheumatoid arthritis. Nanotechnology or nanoparticles used in treatment of rheumatoid arthritis. Mostly focus on application of nanoparticles in treatment of rheumatoid arthritis.